2021
DOI: 10.24815/siele.v8i2.18863
|View full text |Cite
|
Sign up to set email alerts
|

Digital literacy practices in tertiary education: A case of EFL postgraduate students

Abstract: Over the past few decades, technologies grew rapidly, transforming traditional instructions to be more digitalized and stimulating many researchers to study digital literacy practices in a school-educational context. However, studies exploring digital literacy practices in the context of tertiary education are still scarce. Within the qualitative approach, this study investigated digital literacy practices by EFL (English as a Foreign Language) postgraduate students. Moreover, it intensively discusses the kind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 22 publications
2
15
0
Order By: Relevance
“…Knowledge, motivation, and ability in digital literacy also determine the success of student learning (Kumar et al, 2022;Zhu et al, 2022). In line with the results of the above observations of research conducted by previous study that show digital literacy possessed by students also depends on the management of educational institutions or institutions, besides the balance between student motivation and performance influences the perception of this digital literacy (Le et al, 2022;Rinekso et al, 2021). With the gaps and problems above, it is necessary to survey to find out how the perceptions of PGSD UAD students in order to help students improve their digital literacy skills.…”
Section: Introductionsupporting
confidence: 79%
“…Knowledge, motivation, and ability in digital literacy also determine the success of student learning (Kumar et al, 2022;Zhu et al, 2022). In line with the results of the above observations of research conducted by previous study that show digital literacy possessed by students also depends on the management of educational institutions or institutions, besides the balance between student motivation and performance influences the perception of this digital literacy (Le et al, 2022;Rinekso et al, 2021). With the gaps and problems above, it is necessary to survey to find out how the perceptions of PGSD UAD students in order to help students improve their digital literacy skills.…”
Section: Introductionsupporting
confidence: 79%
“…Lecturers, school administrators, and parents can work together and discuss raising this awareness. Parents can participate in developing new technology learning competencies and support children in mastering various educational technologies to achieve learning goals (Rinekso et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The researchers deployed a set of valid and reliable questionnaires to collect the quantitative data on the use of ICT and the perceived impacts of using ICT on students' betterment in learning. Concerning the questionnaire about the use of ICT and the impacts of using ICT, the researchers reviewed several related papers having been published by Alsaleem (2013), Marinoni et al (2020), Rapanta et al (2020), Rinekso et al (2021), andSher Ryn andSC's (2020). The reviews resulted in three coded indicators of using ICT which could be developed into 32 items.…”
Section: Methodsmentioning
confidence: 99%
“…A previous study has also depicted a similar notion about the use of ICT to browse materials. For example, a study conducted by Rinekso et al (2021) demonstrated that their participants made use of ICT, such as the Google search engine, to browse materials. The phonology lecturer in the present study has done a good way by making use of YouTube to browse his materials because audio-visual aids, such as videos, are the best mediator for learning phonological input.…”
Section: Figure 3 Histogram Of Functional Use Of Ictmentioning
confidence: 99%